Sistem Administrasi Perkawinan Beda Negara Pada Dinas Kependudukan Dan Pencatatan Sipil Kota Denpasar - Arsari, Ni Putu Diah; Erviantono, Tedi; Winaya, I Ketut (CITIZEN CHARTER, 2016)
Mixed marriages under Article 57 of Law No. 1 of 1974 on marriage is a marriage between two people in Indonesia are subject to different law because of differences in nationality and one foreign national party and the other party of Indonesian nationality. The purpose of this study was to determine the administrative system of marriage different from the State under the laws of marriage and according to Law No. 24 of 2013 concerning the administration of residence and constraints encountered in meeting the administrative procedure. The research method used is descriptive qualitative research method. Results from this study that there are obstacles in the fulfillment of administrative procedures related to the requirements of mixed marriages validity of a marriage is determined by the respective law and religion so difficult for offenders considered a mixed marriage who have no religion (atheists) as well as omissions in the registration of marriages.Â Â Keywords: Mixed Marriage, Administrative Procedures, the Population Administration, Administration LaÂ